Keefektifan Mmodel Problem Based Learning (PBL) Ditinjau dai Kemampuan Berpikir Reflektif Matematis dan Keyakinan Diri Siswa dalam Menyelesaikan Soal Sistem Persamaan Linear Tiga Variabel (SPLTV) - Rasid, Asrinto; Angkotasan, Nurma; Hamid, Hasan (Jurnal Pendidikan Guru Matematika, 2025)
Study This done with objective for now: (1) How ability think reflective mathematical student after the Problem Based Learning (PBL) model is applied. (2) How confidence self-student after the Problem Based Learning (PBL) model is applied. (3) Is the Problem Based Learning (PBL) model effective reviewed from ability think reflective mathematical and confidence self-student. Type research used is type study experiment. Study This with two groups pretest - posttest design, instruments used form question test and questionnaire student. Samples taken is student class XA has 30 students and class XB has 30 students. Technique deep data collection study This obtained with method see scored score roleh from each class. Whereas technique data analysis using analysis descriptive and analysis inferential. Based on results calculation the ability thinks reflective mathematical on test normality test end obtained sample No normally distributed, then non- parametric testing that is test sign for now ability think reflective mathematical student on class control and class experiment Zh = 28.03 means Zh and Ho rejected H1 accepted It means ability think reflective mathematical student through an effective Problem Based Learning (PBL) model. Confidence self-student in testing hypothesis uses independent sample test, value tcount = 8.575 at level significant 0.05, and dk = (n-1) is obtained ttable = 2.001. so tcount ttable = so that Ha accepted and H0 is rejected, meaning the application of the Problem Based Learning (PBL) model is effective, so can concluded that effective application of the Problem Based Learning (PBL) model reviewed from ability think reflective mathematical and confidence self-student.